Tumourigenesis and resistance to Interferon alpha-treatment in Cutaneous T-cell Lymphoma - Tracey, Lorraine (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2005)
Mycosis fungoides (MF) is a Cutaneous T-Cell lymphoma (CTCL) of unknown aetiology, and the mechanisms of tumourigenesis of this lymphoma are unclear. The diagnosis of MF is extremely challenging due to the fact that, in early stages, it closely resembles many common benign inflammatory skin conditions. Molecular studies of MF are also hampered by the low number of tumoural cells, which infiltrate the skin, with tumoural cells often accounting for less than 5% of the total number of cells in the tissue. At present, no curative treatment is available for MF patients and many commonly used therapeutic strategies achieve remission in only a subset of cases.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin